Lucio Fontana and the Architecture - Antonella Chiazza (Agathón)
This article explores the Spatialism in architectural terms, which is at the base of Lucio Fontana’s work after the Second World War. A fundamental and lesser-known aspect of the artist’s work, developed since 1949, is the creation of ‘Ambienti Spaziali’, really and truly architectural spaces that test the perception and often even the sense of balance of visitors. Thus, the article highlights Fontana’s figure as an environmental artist, investigating the artist’s most intimate work and poetics, a topic often neglected by international critics and not highly considered by the most authoritative sources.